Proportionality in Surat Al-Shams: Thematic Interpretation Style - Salama, Salma Attia Muhammad; Soude, Khadeja Mohamed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This research is intended to study the proportionality in Surat Al-Shams, and proportionality is intended verbal and moral proportionality of Surat Al-Shams by knowing the reasons for the arrangement of the surah and its compatibility, and the verses of the one surah and its compatibility, and the combined face between the beginning of the sura and its section, based on the inductive analytical approach to reveal the relationships that link the topics of this surah and its purposes, and show the intellectual pattern regulating its meanings and buildings, and the research reached a set of results, the most prominent of which was that the proportion in Surat Al-Shams between the strength of connection and interdependence of the verses of Surat Al-Shams, and even the strength of The interconnection of Surat Al-Shams with what preceded it (Surat Al-Balad) and with what follows (Surat Al-Lail), and in that it responded to those who challenge the verses of God (, and the faces of rhetorical miracles deposited in the arrangements and links, which contributed to understanding its intention with the shortness of its verses, but it includes great meanings and directives, calling for the goodness of the individual with his community, and his cooperation to stay away from falling into what causes the wrath of God and show the good consequence of the one who pays tribute to himself, and the bad consequence of those who follow his whims.
Keywords: Proportion; Surat Al-Shams; Moral; Verbal